AB0913 Lower objective physical activity in patients with axial spondyloarthritis compared to healthy controls is independent of disease activity. (23rd January 2014) - Swinnen, T.; Scheers, T.; Lefevre, J.; Dankaerts, W.; Westhovens, R.; de Vlam, K.
Abstract : Background: Traditionally, measures of physical function assess the capacity to execute daily activities in patients with axial SpondyloArthritis (aSpA) 1 . How many activities that result in energy expenditure patients perform in their real-life environment (i.e. movement-related participation) is not known. Objectives: To compare physical activity between patients with aSpA and healthy controls. To evaluate the contribution of disease activity to physical activity. Methods: Physical activity was compared between 40 patients with aSpA and 40 healthy, age and sex matched controls during five consecutive days (three weekdays and two weekend days) using the SenseWear Armband. Disease activity was measured by the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). Differences in physical activity between patients with aSpA and healthy controls were examined with Wilcoxon signed- rank tests and a mixed linear model. To appreciate interaction effects, differences scores between patients and healthy controls were correlated with disease activity. Results: Average weekly physical activity level (MET, p<0.05) and energy expenditure (MET.hours/day, p<0.05) were significantly lower in patients with aSpA. Weekly averages of vigorous and very vigorous physical activities were significantly lower in patients with aSpA (both p<0.001). No differences between groups were found for inactivity and time spent at light or moderate activities. Disease activity did not interact with differences in physical activity between patients with aSpA and healthy controls, evidenced by non-significant and very low correlations between BASDAI and healthy controls-aSpA patients' difference scores. Conclusions: Patients with aSpA exhibit lower physical activity compared to healthy controls. These differences are independent of disease activity, suggesting a window of opportunity to develop tailored physical activity interventions for this patient group in addition to medical care. Also, objective physical activity monitoring is a promising outcome measure in aSpA. References: Sigl T, Cieza A, van der Heijde D, Stucki G. ICF based comparison of disease specific instruments measuring physical functional ability in ankylosing spondylitis. Ann Rheum Dis. 2005;64(11):1576-81. Disclosure of Interest: None Declared